THE DEVELOPMENT OF A POSITIVE STRATEGY FOR SELF-MANAGEMENT TO ENHANCE NEW NORMAL WELL-BEING IMMUNITY OF DIABETES MELLITUS PATIENTS - Surapichpong, Chaiyanut; Malakul Na Ayudhya, Prasarn; Kirdpitak, Pongpan (Thai Interdisciplinary and Sustainability Review, 2024)
This basic mixed method research design aimed to develop a positive strategy for self-management to enhance new normal well-being immunity of diabetes mellitus patients. The sample group was diabetes mellitus patients in Samut Prakan Province; 847 cases were recruited from multi-stage sampling. The research results were as follows: 1) Results of the Confirm Factor Analysis (CFA) study of the well-being immunity of the new normal diabetes mellitus patients were consistent with the empirical data with a construct reliability ρc of 0.820 and the average variance extraction ρv of 0.559. 2) The total mean score of well-being immunity of the new normal diabetes mellitus revealed a mean level 3) The positive strategy for self-management was developed by integrating the positive psychology concept, the self-management concept, and the concept of health literacy, 4) The new normal well-being immunity of diabetes mellitus patients of the experimental group in posttest and follow-up were significantly higher than the pretest at .01 level and significantly higher than that of the control group at .01 level.